FREQUENCY OF IRON OVERLOAD COMPLICATIONS IN BETA THALASSEMIA MAJOR PATIENTS - Shah, Salva; Farooq, Nazish; Basharat, Adeel; Shah, Maheen; Mukhtiar, Syed; Farhad, Sadia (Journal of Postgraduate Medical Institute, 2019)
Objective: To study the frequency of iron overload related complications in beta thalassemia major patients on chelation therapy in Fatimid Foundation, Peshawar. Methodology: This cross-sectional study was conducted at Fatimid Foundation, Peshawar between June 2015 to August 2015. One hundred confirmed beta (Î²) thalassemia major patients were enrolled in this study. Their detailed history and physical examination including height and weight was recorded on pre-designed questionnaire. Blood samples were analysed for calcium and phosphorus. Levels of thyroid stimulating harmone (TSH) and thyroxin (free T4), random blood glucose, ECG, x-rays and echocardiography were all noted and positive cases of short stature, hypothyroidism, hypoparathyroidism, diabetes mellitis and cardiac dysfunction were recorded. Data were analysed using SPSS. Results: Out of 100 patients, 53% were males and 47% were females. The age range of patients was 5 to 20 years (mean 13.62 ±3.78 years). Short stature was seen in 89% patients, hypoparathyroidism in 26% patients, hypothyroidism in 10%, cardiac dysfunction in 9% and diabetes mellitus in 5% patients. Conclusion: The frequency of frequency of iron overload related complications in beta thalassemia major patients was relatively higher in this study. Short stature was the most frequent complication while diabetes mellitus was the least common complication.